Profil literasi sains awal mahasiswa calon guru biologi di Universitas 17 Agustus 1945 Banyuwangi: (Science literacy profile of prospective biology teacher in Universitas 17 Agustus 1945 Banyuwangi) - Muhimmatin, Ifa; Prasetiyo, Totok Hari (BIODIK, 2024)
Scientific literacy is an important ability for prospective biology teachers. This research was conducted to determine the profile of the initial scientific literacy abilities of prospective biology teachers. This research is a quantitative descriptive study, with 24 research subjects from second-semester students of the biology education, Universitas 17 Agustus 1945 Banyuwangi. This research uses the Test of Scientific Literacy Skills (TOSLS) instrument developed by Gormally, et al. with a questionnaire theme about general biology. Data was obtained from filling out the questionnaire, and analyzed using percentages and categorization. The results of the research show that the initial scientific literacy abilities of prospective biology teacher students at the University of 17 August 1945 Banyuwangi are in the low category with a percentage of 30.24%. Students have relatively good literacy skills in evaluating the use and misuse of scientific information. Students have very poor literacy skills when faced with quantitative data. The lack of student abilities related to quantitative data can be a concern for course lecturer so that they can encourage students' scientific literacy abilities through the learning process. Abstrak. Literasi sains merupakan kemampuan yang penting dimiliki oleh mahasiswa calon guru. Tujuan penelitian ini ialah untuk mengetahui profil kemampuan awal litarasi sains mahasiswa calon guru. Penelitian ini merupakan penelitian deskriptif kuantitatif, dengan subyek penelitian ialah 24 mahasiswa semester 2 program studi pendidikan biologi Universitas 17 Agustus 1945 Banyuwangi. Penelitian ini menggunakan instrumen Test of Scientific Literacy Skills (TOSLS) yang dikembangkan oleh Gormally, dkk. dengan tema kuesioner tentang biologi umum. Data yang diperoleh dari hasil pengisian kuesioner dianalisis menggunakan persentase dan kategorisasi. hasil penelitian menunjukkan bahwa kemampuan awal literasi sains mahasiswa calon guru biologi Universitas 17 Agustus 1945 Banyuwangi secara keseluruhan termasuk dalam kategori rendah dengan persentase 30,24%. Mahasiswa mempunyai kemampuan literasi yang tergolong baik dalam hal mengevaluasi penggunaan dan penyalahgunaan informasi ilmiah. Mahasiswa mempunyai kemampuan literasi yang sangat kurang ketika dihadapkan pada data kuantitatif. Kurangnya kemampuan mahasiswa yang berkaitan dengan data kuantitatif ini dapat menjadi perhatian bagi pengampu matakuliah agar dapat mendorong kemampuan literasi sains mahasiswa melalui proses pembelajaran.